(3dhGeY GdCfhGQ Ydi UMGM GdCNHGQs - (3TeS GdOjf CHh YHO Gddg eMeO Hf eMeO GdehUdj GdTGaYjs; (3GdbGVj YjGV GdjMUHj,J (B544 (3g` s ((3LGeY GdCQR ai (B_ (3HWQGHdS GdeMQhSI s)
(3ChdgG (B:s
(3hHYO aGdMOjK HMQ RGNQ Jdbi Hg GdLhGgQ GdahGNQ dGSjeG GdehWC GdehWi SHd Yde aVdg eHOC s
(3BNQgG (B:s
(3hGfg jchf fhQ GdegJOi EPG eWdY GdCfhGQ TgQ GdehdO hCf jVF ddYdhe HUQi ceG CVGAJ ai QHjY HUQi hGdMeO ddg ChdkG hBNQkG XGgQkG hHGWfkG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3YhQVJ Ydi fSNI HNW GdeUfa hUMMJ HgG eTgG MhGTi cKjQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs